A 2.016-Gb/s Crystal-Less IR-UWB Transceiver for Free-Moving Subject With High-Density Neural Implant - Lei, Jiaxin; Wu, Yusong; Liu, Xiliang; Zhang, Bingjing; Pei, Ruixuan; Zhang, Yuwei; Ma, Xiaoyan; Zhang, Milin (IEEE journal of solid-state circuits, 2025)
This article presents a compact crystal-less impulse radio ultra-wideband (IR-UWB) transceiver designed for free-moving subjects with high-density neural implants. A six-order hybrid modulation scheme, combining differential 16-pulse-position modulation (D16PPM) and four-pulsewidth modulation (4PWM), is proposed, enabling a maximum data rate of 2.016Gb/s. An intra-pulse frequency hopping (FH) technique is proposed to precisely adjust the frequency variations within a single pulse, achieving a maximum transmitter (TX) radiation power of −7.6 dBm under the spectral mask. The all-digital TX consumes only 3.79 mW, resulting in an energy efficiency of 1.9 pJ/bit. A two-stage time-to-digital converter (TDC) is designed for the receiver (RX), featuring a sub-10-ps resolution and supporting both rising and falling edge conversions for the hybrid demodulation. With a power consumption of 17.1mW, the RX achieves an energy efficiency of 8.5 pJ/bit. The transceiver also incorporates a wireless clock calibration strategy, enabling a crystal-referenced external base station to wirelessly calibrate the clock frequency of the crystal-less implant. The calibration process completes within several microseconds, after which the implant can turn off the RX and the all-digital phase-locked loop (ADPLL) to reduce the power consumption. Ex vivo test demonstrates that the transceiver supports a transcutaneous transmission distance of 40 cm at 2.016 Gb/s and 120 cm at 1.344Gb/s, enabling the experimental subject to move freely within a meter-scale range while maintaining a Gb/s-level data rate.